Facile Synthesis of a Nickel Sulfide (NiS) Hierarchical Flower for the Electrochemical Oxidation of H2O2 and the Methanol Oxidation Reaction (MOR). Issue 4 (1st January 2017) - Zhang, Jingchao; Xu, Chunying; Zhang, Daojun; Zhao, Jingli; Zheng, Shuxian; Su, Huimin; Wei, Feifei; Yuan, Baiqing; Fernandez, Carlos
Abstract : The synthesis of a novel hierarchical flower-like NiS via a solvothermal method for the electrochemcial oxidation of H2 O2 on a carbon paste electrode with high catalytic activity for the (MOR) in an alkaline medium has been reported. Novel nickel sulfide (NiS) hierarchical flower-like structures were characterized by X-ray diffraction, scanning electron microscope, and transmission electron microscopy. A carbon paste electrode was modified with the as-prepared hierarchical flower-like NiS, resulting in a high electrocatalytic activity toward the oxidation of H2 O2 . The NiS-modified electrode was used for H2 O2 sensing, which was achieved over a wide linear range from 0.5 μM to 1.37 mM (I/μA = −0.19025 + 0.06094 C/mM) with a low limit of detection (LOD) of 0.3 μM and a limit of quantitation (LOQ) of 0.8 μM. The hierarchical flower-like NiS also exhibited a high electrocatalytic activity for the methanol oxidation reaction (MOR) in an alkaline medium with a high tolerance toward the catalyst-poisoning species generated during the MOR. The MOR proceeded via the direct electrooxidation of methanol on the oxidized NiS surface layer because the oxidation peak potential of the MOR was more positive than that of the oxidation of NiS.